Decomposition of Post-Pandemic Gender Wage Gaps in Indonesia: an Analysis Across the Wage Distribution - Ruslan, Kadir; Sukma, Weni Lidya (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
This study examines post-pandemic gender wage gaps in Indonesia using SAKERNAS data from 2018 to 2023. OLS and RIF-OLS regression results indicate that gender wage gaps widened post-pandemic, with female employees earning 30 percent less than their male counterparts on average, narrowing to 23 percent after controlling for wage-related characteristics. The gap is most pronounced among low-paid workers, where women earned 40 to 50 percent less than men. Decomposition analysis across the wage distribution reveals that the majority of the gap is driven by unexplained factors, reinforcing the persistence of the